2018
DOI: 10.3390/molecules23102621
|View full text |Cite
|
Sign up to set email alerts
|

Effect of High Pressure Treatment on Poly(lactic acid)/Nano–TiO2 Composite Films

Abstract: The microstructure, thermal properties, mechanical properties and oxygen and water vapor barrier properties of a poly(lactic acid) (PLA)/nano-TiO2 composite film before and after high pressure treatment were studied. Structural analysis showed that the functional group structure of the high pressure treated composite film did not change. It was found that the high pressure treatment did not form new chemical bonds between the nanoparticles and the PLA. The micro-section of the composite film after high pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 36 publications
2
11
0
Order By: Relevance
“…Such results were reflected in the new clay‐based nanocomposites reported by Sanchez‐Garcia and Lagaron 34 . Some studies have reported similar behavior of PLA nanocomposites filled with nano‐TiO 2 , in which OP was significantly reduced when 50 g kg −1 nano‐ZnO was loaded 35 …”
Section: Resultsmentioning
confidence: 53%
“…Such results were reflected in the new clay‐based nanocomposites reported by Sanchez‐Garcia and Lagaron 34 . Some studies have reported similar behavior of PLA nanocomposites filled with nano‐TiO 2 , in which OP was significantly reduced when 50 g kg −1 nano‐ZnO was loaded 35 …”
Section: Resultsmentioning
confidence: 53%
“…The surface and other mechanical properties of products made from PLA or composite filaments were investigated previously ( Graupner, Herrmann & Müssig, 2009 ; Chi et al, 2018 ; Ivanov et al, 2019 ; Wang et al, 2016 ). However, the microstructure of 3D-printed PLA objects is highly dependent on the printing parameters, and it is not possible to predict the structure and porosity of a particular object based on published data.…”
Section: Discussionmentioning
confidence: 99%
“…1). The surface and other mechanical properties of products made from PLA or composite filaments were investigated previously (Graupner et al 2009;Chi et al 2018;Ivanov et al 2019;Wang et al 2016). However, the microstructure of 3D-printed PLA objects is highly dependent on the printing parameters, and it is not possible to predict the structure and porosity of a particular object based on published data.…”
Section: Discussionmentioning
confidence: 99%